Implementasi Digital Marketing Pada Pemasaran Produk Olahan Bambu Di Desa Kotapulu Kecamatan Dolo - Muhammad Hasyim B. Dg. Matutu; Farid Farid; Anisah Anisah (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
MBKM independent village development is a form of community service with the aim of building and optimizing the potential of the village through the implementation of digital marketing from the knowledge learned by students in the scope of higher education. Kotapulu village has the potential for forest products that are quite abundant, one of which is bamboo. Forest products obtained by the community are utilized by making processed bamboo products. Various kinds of processed products from bamboo such as chairs, tables and curtains made of bamboo. The lack of public knowledge about the use of digital marketing encourages MBKM to develop villages to provide assistance and training. From the results of the program implemented by MBKM to build kotapulu village, to increase public insight into the importance of using social media as a means of promoting processed bamboo products, as well as a means to increase competitiveness in industry 4.0.